CSR DISCLOSURE, PROFITABILITY AND SOLVENCY TOWARDS FIRM VALUE - Fatimah Fatimah; Dadan Sukardan (JRAK, 2018)
The Purpose of this research is to empirically examine the effect of CSR Disclosure, Profitability and Solvency towards Firm Value on Mining Company listed in Stock Exchange of each country in ASEAN in 2006-2013. The sampling method used in this research is purposive sampling with criteria of companies that issued their financial and CSR report during the period of 2006-2013. Data obtained from Stock Exchange of each country in ASEAN with the period of 2006 to 2013 and total population of 54 companies. Analysis techniques used in this research is multiple linear regression analysis and hypothesis testing used is partial test (t test) with a significance level of 5% and coefficient of determination test. Statistical test results showed that CSR Disclosure, Profitability and Solvency have no significant effect towards Firm Value.